Body dysmorphic disorder: symptoms, models and treatment - Kollei, Ines; Martin, Alexandra; Erim, Yesim (Psychotherapie Psychosomatik Medizinische Psychologie, 2014)
EVALuna2:24024

Classification of body dysmorphic disorder - What is the advantage of the new DSM-5 criteria? - Schieber, Katharina; Kollei, Ines; De Zwaan, Martina; Martin, Alexandra (Journal of psychosomatic research, 2015)
In DSM-5 the diagnosis of body dysmorphic disorder (BDD) has been subjected to two important changes: Firstly, BDD has been assigned to the category of obsessive-compulsive and related disorders. Secondly, a new criterion has been defined requiring the presence of repetitive behaviors or mental acts in response to appearance concerns. The aims of this study were to report the prevalence rates of BDD based on a DSM-5 diagnosis, and to evaluate the impact of the recently introduced DSM-5 criteria for BDD by comparing the prevalence rates (DSM-5 vs.BDD-criteria (DSM-IV/DSM-5), dysmorphic concerns, and depressive symptoms, were assessed in a representative sample of the German general population (N=2129, aged 18-65years).The association between BDD case identification based on DSM-IV and DSM-5 was strong (Phi=.95, p<.001), although point prevalence of BDD according to DSM-5 was slightly lower (2.9%, n=62 vs. 3.2%, n=68). Approximately one third of the identified BDD (DSM-5) cases reported time-consuming behavioral acts in response to appearance concerns. In detail, 0.8% of the German general population fulfilled the BDD criteria and reported repetitive acts of at least one hour/day.The revised criteria of BDD in DSM-5 do not seem to have an impact on prevalence rates. However, the recently added B-criterion reflects more precisely the clinical symptoms of BDD, and may be useful for distinguishing between various severity levels related to repetitive behaviors/mental acts.
EVALuna2:24017